Destination competitiveness: what we know, what we know but shouldn't and what we don't know but should. Issue 6 (11th May 2016) - Abreu-Novais, Margarida; Ruhanen, Lisa; Arcodia, Charles
Abstract : Two decades after the seminal work of Crouch and Ritchie [(1999). Tourism, competitiveness, and societal prosperity. Journal of Business Research, 44 (3), 137–152], which triggered an avalanche of research on the topic, there is an extensive and still-growing body of literature on destination competiveness. Research on competitiveness, in the context of tourism destinations and even in its parent field of economics, has been characterized by controversy and strong criticism. Given the complexity of the phenomenon, the multiplicity of perspectives taken on it and the current stage of knowledge, there is a clear need for a reflective audit that enables a careful consideration on the knowledge acquired with past research as well as a well-thought-out identification of the needs for future research. Only such meticulous process will ensure the progress of this field of enquiry. The wide-spread acknowledgement of the importance of competitiveness for a destination's long-term success in addition to the constant comments that it is still a topic not well understood, suggests that research on it still has a long future ahead. This article embraces this challenging task by documenting, examining and critically assessing the existing literature on three dimensions: definitions, theoretical models and measurement. In addition, existing gaps are identified and research propositions are presented to guide future research.